2007
DOI: 10.1002/cncr.22545
|View full text |Cite
|
Sign up to set email alerts
|

A phase II and pharmacodynamic study of gefitinib in patients with refractory or recurrent epithelial ovarian cancer

Abstract: BACKGROUNDThe primary objective of this study was to evaluate the biochemical effects of gefitinib on its target signal‐transduction pathways in patients with recurrent epithelial ovarian cancer (EOC). The secondary objectives included assessing clinical activity and toxicity and determining the association between biochemical and clinical outcomes.METHODSTwenty‐four heavily pretreated patients with EOC who had good end‐organ function and performance status and who had measurable disease received gefitinib 500… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
89
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(93 citation statements)
references
References 42 publications
4
89
0
Order By: Relevance
“…A similar finding was observed in our Phase II study of single-agent gefitinib in ovarian cancer. 49 Our findings validate in vitro studies from Matei et al, who demonstrated that AKT activation typically occurs after therapy with imatinib mesylate. 34 The power of our findings, however, rests in the ability to demonstrate this impact on molecular signaling in a prospective fashion in patient tumor samples.…”
Section: Discussionsupporting
confidence: 90%
“…A similar finding was observed in our Phase II study of single-agent gefitinib in ovarian cancer. 49 Our findings validate in vitro studies from Matei et al, who demonstrated that AKT activation typically occurs after therapy with imatinib mesylate. 34 The power of our findings, however, rests in the ability to demonstrate this impact on molecular signaling in a prospective fashion in patient tumor samples.…”
Section: Discussionsupporting
confidence: 90%
“…Small molecule tyrosine kinase inhibitors (TKI) targeting EGFR activity have been investigated in several trials specifically focused on ovarian cancer (Table 4). Single agent TKI did not show any substantial clinical benefit (0-9% for gefitinib (Posadas et al 2007, Schilder et al 2005, 0% for CI-1033 an irreversible EGFR inhibitor (Campos et al 2005)). TKIs combined with cytotoxic chemotherapy, anti-angiogenic therapy, or hormonal therapy have also shown limited clinical efficacy and in some cases excessive toxicity (Campos et al 2010, Chambers et al 2010, Nimeiri et al 2008, Vasey et al 2008.…”
Section: Epidermal Growth Factor Receptorsmentioning
confidence: 93%
“…The other enrolled 24 patients and no clinical responses were observed [25] . There are currently no ongoing trials.…”
Section: Gefitinibmentioning
confidence: 99%
“…There were 2 Phase II trials evaluating the efficacy of gefitinib in recurrent metastatic endometrial cancer, however, they showed that it lacked sufficient efficacy to warrant further evaluation [24,25] . One of the trials enrolled 29 patients, of which one had a complete response, however, it was not associated with an ErbB mutation [24] .…”
Section: Gefitinibmentioning
confidence: 99%